A Block Based Novel Digital Video Watermarking Scheme Using DCT (International Journal of Engineering and Computer Science, 2014)
In recent year, almost maximum work is done on internet and many number of images, audios, videos is distributed over the network, so there may be chances to piracy this data and may be chance to perform illegal operation such as duplication, modification etc. So information hiding techniques become more important. For this we are using digital video watermarking scheme.  In digital watermarking scheme, some type of digital data such as logo, name or label called as watermark which represent author’s ownership are embedded into desire host image. Here adding information to protect copyright, to authenticate, to prevent misuse etc. Afterword watermarked data extracted by extraction process.